Mobile for good : a how-to fundraising guide for nonprofits - Mansfield, Heather (McGraw-Hill Education, 2014)
"Even if you can only invest 5 staff hours and a mobile and social media budget of $1,000 annually, your nonprofit must invest in mobile and social media." -- Heather Mansfield Mobile devices are fast becoming the #1 means of digital communication. If you want a sustainable future for your nonprofit, you need to have a strong presence on prospective donors' tablets and smartphones. Statistics prove that the most successful online fundraising campaigns are those designed for portable devices--from 2-inch smartphone screens to 17-inch laptops. In this groundbreaking book, social media pioneer Heather Mansfield offers everything you need to know to conceptualize, build, and maintain a mobile and social fundraising strategy to dramatically increase donations. In Mobile for Good, Mansfield takes you step by step through the entire process. Learn how to: Master your mobile fundraising strategy Create a strategic plan flexible enough to handle changes in technology Design a website and emails that work on both mobile devices and computers Choose the best mobile and online tools based on your budget and your donor demographics Build a system that tracks, evaluates, and reports campaign results Maximize the potential of Facebook, Twitter, LinkedIn, and other sites Whether your goal is to raise more funds online, launch a new program, or increase your capacity to maintain current operations, creating and executing a mobile and social media strategy is a small investment that packs a big punch. Apply the lessons of Mobile for Good , and your organization can and will raise more funds than ever. ADVANCE PRAISE FOR MOBILE FOR GOOD : "If I want to know what's trending, research current best practices, or discover new tools relevant to nonprofit technology, Heather Mansfield's blog Nonprofit Tech for Good and her books are always my top references. -- Viviana Pagán-Muñiz, Digital Marketing Director, SOS Children's Villages-USA "Social Media for Social Good and her blog Nonprofit Tech for Good have been my primary resources for learning how to communicate Indian conservation issues on a global scale. Thanks to Heather Mansfield's advice, we've been able to build an international brand from our tiny corner of the world." -- Vinay Datla, Director of Communications, Wildlife SOS-India "Heather Mansfield's @NonprofitOrgs online accounts have become my go-to resource for connecting with other nonprofits as well as staying informed with the latest trends in mobile ...